2003
DOI: 10.2172/918261
|View full text |Cite
|
Sign up to set email alerts
|

Enhancements for distributed certificate authority approaches for mobile wireless ad hoc networks.

Abstract: Mobile wireless ad hoc networks that are resistant to adversarial manipulation are necessary for distributed systems used in military and security applications. Critical to the successful operation of these networks, which operate in the presence of adversarial stressors, are robust and efficient information assurance methods. In this report we describe necessary enhancements for a distributed certificate authority (CA) used in secure wireless network architectures. Necessary cryptographic algorithms used in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Furthermore, it is vulnerable to adversaries because it is a single and independent node that can be attacked easily. For the problem of availability Anderson et al [4] suggested an approach in which CAs are assigned to the nodes repeatedly. While it seems that this technique may solve the availability problem (because the network will be working well as long as 12 there is just one node in the MANET), this approach may become unstable when the nodes are trying to find each other in the network.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is vulnerable to adversaries because it is a single and independent node that can be attacked easily. For the problem of availability Anderson et al [4] suggested an approach in which CAs are assigned to the nodes repeatedly. While it seems that this technique may solve the availability problem (because the network will be working well as long as 12 there is just one node in the MANET), this approach may become unstable when the nodes are trying to find each other in the network.…”
Section: Introductionmentioning
confidence: 99%